Edema treatment, rational and physiological use of diuretics - Tapia, Hugo R. (2022)
Diuretics are pharmacological agents used to treat edematous conditions. Their primary mechanism of action is to reduce sodium renal reabsorption and to promote its excretion. The rational and physiological use of diuretics require a basic knowledge of their pharmacokinetics and pharmacodynamic profile, as well as their possible side effects and complications. Although diuretics are used for non-edematous conditions, the main focus of this article is on the diuretics use for clinical conditions associated with the expansion of the extracellular compartment, associated with the development of edema.